تطبیقات تقنیة التعریف بترددات الرادیو RFID فى مکتبات جامعة المجمعة بالمملکة العربیة السعودیة : دراسة حالة - د. أسامة محمد عطیة خمیس (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aimed to identify the stages of Radio Frequency Identification (RFID) technology application in Majmaah University Libraries in Saudi Arabia and pinpoint the obstacles that faced the staff during its adoption, as well as state the steps followed to overcome such obstacles. The study is based on two methodologies; i.e., the first is the case study as a primary tool to collect data on the application of projects related to RFID in the Majmaah University libraries, and the second is a field survey.The study concluded with a set of results, from the most important are: (i) the definition radio frequency techniques helped staff in shorten the borrowing procedures as well as the inventory, and facilitate the self-borrowing, (ii) the staff are committed to achieve the first self-study recommendations on the existence of an effective internal control system .This study recommends that there is a need to (i) convert all libraries at Majmaah University to be based on radio frequency RFID technology, (i) set a plan to train the staff to cope with the using of the definition of radio frequency RFID,